Studi Timbulan, Komposisi dan Karakteristik Sampah Institusi di UPN Veteran Yogyakarta - ika wahyuning widiarti; Titi Tiara Anastasia; Arih Fitra Cahayani; Fairus Jelita Regita Putri; Khauroun Nazilatul Udhma; Nadya Ulima; Praditya Anggi Widhiananto; Raden Ajeng Larasati; Veronika Cendi Prameswari Putri; Arsiva Alifia Gati; Aulia Syifa Ardiati; Dzulfiqar Izzatur Rahman; Glorya Mega Mandang; Tyka Ramadhamayanti; Supriansyah Supriansyah; Urbanilisa Fredlina Halawa (Jurnal Mineral, Energi dan Lingkungan, 2022)
UPN “Veteran” Yogyakarta does not apply a sustainable solid waste management system. Waste is only carried out by storing, collecting, and transporting to TPA Piyungan. The purpose of this study was to determine the generation, composition and characteristics of waste and to provide recommendations for sustainable waste management strategies on the UPNVY campus. The method of measuring waste generation and composition refers to SNI 19-3964-1994. Waste characteristics were analyzed by proximate test and ultimate test. The results of the survey and measurements showed that the waste generation at UPNVY was 135.45 kg/day covering Campus I Condong catur at 96.66 kg/day and Campus II Babarsari at 37.79 kg/day. The composition of waste consists of organic waste (24.840%), paper (23.499%), soft plastic (7.450%), hard plastic (5.673%), plastic bag (9.129%), metal (1.294%), glass (1.392%), hazardous waste (0.512%), other waste (9.289%), and residue (16.922%). The proximate test showed that the highest moisture content was in food waste, the highest volatile content and calorific value were found in hard plastic. Meanwhile, the lowest ash content in soft plastic and the lowest fixed Carbon content was owned by plastic bag. For the ultimate test, plastic waste has the highest C and H content. The recommended sustainable waste management strategies are waste reduction and sortation; provision of sorted trash cans, processing of organic waste into compost; and construction of 3R TPS.